Impact of residual risk messaging to reduce false reassurance following test-negative results from asymptomatic coronavirus (SARS-CoV-2) testing: an online experimental study of a hypothetical test - Leah Ffion Jones; Richard Amlot; Dale Weston; Holly Carter; Theresa Marteau; Natalie Gold; Eleonore Batteux; Stefanie Bonfield (BMJ Open)
Objectives Individuals who receive a negative lateral flow coronavirus test result may misunderstand it as meaning ‘no risk of infectiousness’, giving false reassurance. This experiment tested the impact of adding information to negative test result messages about residual risk and the need to continue protective behaviours.Design. 4 (residual risk) × 2 (post-test result behaviours) between-subjects design.Setting. Online.Participants 1200 adults from a representative UK sample recruited via Prolific (12–15 March 2021).Interventions Participants were randomly allocated to one of eight messages. Residual risk messages were: (1) ‘Your coronavirus test result is negative’ (control); (2) message 1 plus ‘It’s likely you were not infectious when the test was done’ (current NHS Test & Trace (T&T); (3) message 2 plus ‘But there is still a chance you may be infectious’ (elaborated NHS T&T); and (4) message 3 plus infographic depicting residual risk (elaborated NHS T&T+infographic). Each message contained either no additional information or information about the need to continue following guidelines and protective behaviours.Outcome measures (1) Proportion understanding residual risk of infectiousness and (2) likelihood of engaging in protective behaviours (scales 1–7).Results The control message decreased understanding relative to the current NHS T&T message: 54% versus 71% (Adjusted Odds Ratio (AOR)=0.56 95% CI 0.34 to 0.95, p=0.030). Understanding increased with the elaborated NHS T&T (89%; AOR=3.25 95% CI 1.64 to 6.42, p=0.001) and elaborated NHS T&T+infographic (91%; AOR=5.16 95% CI 2.47 to 10.82, p<0.001) compared with current NHS T&T message. Likelihood of engaging in protective behaviours was unaffected by information (AOR=1.11 95% CI 0.69 to 1.80, χ2(1)=0.18, p=0.669), being high (M=6.4, SD=0.9) across the sample.Conclusions A considerable proportion of participants misunderstood the residual risk following a negative test result. The addition of a single sentence (‘But there is still a chance you may be infectious’) to current NHS T&T wording increased understanding of residual risk.Trial registration number OSF: https://osf.io/byfz3/